Renal fat fraction is significantly associated with the risk of chronic kidney disease in patients with type 2 diabetes - Shen, Yan; Xie, Lianghua; Chen, Xiangjun; Mao, Lina; Qin, Yao; Lan, Rui; Yang, Shumin; Hu, Jinbo; Li, Xue; Ye, Hanwen; Luo, Wenjin; Gong, Lilin; et al. (Frontiers in Endocrinology, 2022)
Backgrounds: Ectopic fat deposition is closely related to chronic kidney disease (CKD). Currently, there are few population studies that have been conducted to determine the relationship between renal parenchyma fat deposition and the risk of CKD among patients with type 2 diabetes mellitus (T2DM). Therefore, we employed magnetic resonance imaging (MRI) to detect renal parenchyma fat content in individuals with T2DM, expressed as renal fat fraction (FF), to explore whether renal FF is an important risk factor for CKD in patients with T2DM. Methods: In this cross-sectional study, 189 subjects with T2DM were enrolled. CKD was defined as the estimated glomerular filtration rate (eGFR)＜60 mL/min/1.73m2. Measurement of the renal FF was performed on a 3.0-T MRI (MAGNETOM Skyra, Siemens, Erlangen, Germany). Binary logistic regression was used to determine the association between tertiles of renal FF and risk of CKD. Receiver-operator characteristic (ROC) curves were constructed to evaluate the sensitivity and specificity of renal FF in detecting CKD in T2DM patients. Results: The patients were divided into three groups according to tertiles of the renal FF level (2.498 - 7.434). As renal FF increases, patients tend to be older, and more abdominally obese, with a decreased eGFR (p＜0.05). After adjustment for potential confounders, patients in the highest tertile of renal FF had a significantly increased risk of CKD than those in the lowest tertile (odds ratio (OR) = 3.98, 95% confidence interval (CI) = 1.12 - 14.09, p = 0.032), and the area under the ROC curve for this model was 0.836 (0.765–0.907). Conclusions: The renal FF is significantly independently associated with CKD in patients with T2DM.